Determinacion de la capacidad antioxidante in vitro del decocto de la coronta de zea mays l. (variedad morado)” - Bartolo Argomedo, Roxana Noemi (2010)
It has been reported that some compounds of plant origin fenolite present inside the cell antioxidant activity, reducing the concentration of free radicals. This study aims to determine the antioxidant capacity of the decoction of the cobs of Zea mays L. (Purple variety), for which we used the method of Brand - Williams. The cobs of Zea mays L. (Purple variety), were collected in the District of Cajabamba, Department of Cajamarca. First the sample was selected, dried in an oven and then milled to a powder, from which was prepared and filtered decoct. The filtrate was prepared four different concentrations (7.5, 15, 30, 60% v/v). From each of them made the absorbance readings in the spectrophotometer Jenway, to 515 nm, with these data we calculated the percentage of inhibition at 0 and 30 minutes. The antioxidant capacity of Zea mays L. decoct purple increases with increasing concentration of the extract